Current approaches to assess HIV-1 persistence. Issue 4 (July 2016) - Banga, Riddhima; Procopio, Francesco A.; Perreau, Matthieu
Abstract : Purpose of review: The persistence of HIV within long-lived HIV-infected CD4 + T cells is the primary obstacle towards HIV eradication and numerous strategies are currently being evaluated to target and kill HIV-infected cells to ultimately find a cure. HIV reservoirs are classically quantified by standard methods such as integrated HIV DNA (Alu PCR) and/or quantitative viral outgrowth assay; however, recent technical advances may offer new opportunities to comprehensively assess the impact of clinical interventions. Recent findings: Digital droplet PCR, tat/rev-induced limiting dilution analysis, enhanced quantitative viral outgrowth assay, and whole genome sequencing technologies offer increased precision and/or higher sensitivity to quantify and characterize HIV reservoirs in antiretroviral therapy-treated HIV-infected patients. Summary: The objective of this review is to highlight the characteristics and limits of recent technical advances that may help to monitor the impact of clinical interventions in antiretroviral therapy-treated patients.